Peran Notaris Dalam Transformasi Digital Dalam Rangka Kesejahteraan Masyarakat Indonesia - Nanda Dwi Rizkia; Hardi Fardiansyah (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Indonesia has a variety of genetic resources and traditional knowledge related to genetic resources that are abundant and have economic value so that they need to be preserved and developed so that they can be utilized in a sustainable manner as development resources for the greatest possible benefit and prosperity of the people, normative juridical research methods, a process to find legal rules, legal principles and legal doctrines to answer the legal issues at hand, the results of research on the Nagoya protocol are international agreements in the field of environment within the framework of the convention on biodiversity which regulate access to genetic resources and the sharing of benefits fair and balanced between beneficiaries and providers of genetic resources based on mutual agreement, the main problem is the reduction of the community's right to access in obtaining the right to a good and healthy environment, be it the right to information, the right to participate i, as well as the right to justice. In addition, there is a concept error in the formulation of strict liability which can result in difficulties implementing the concept. Eliminating the exceptions to the prohibition against burning for traditional farming communities has the potential to criminalize and shift the burden of responsibility.